Impact of AM fungi and Rock-phosphate on mycorrhizal colonization, growth and nutrition of Tylophora indica (Burm. f.) Merril. under glass house conditions - and C. MANOHARACHARY*, K. SHARATHBABU (Indian Phytopathology, 2006)
An investigation was carried out on the mycorrhizal colonization, growth and nutrition of Tylophora indica (T. indica) inoculated with Glomus fasciculatum (GF) and rock phosphate (RP) in nutrient deficient sterilized soil using earthen pots under glasshouse conditions. Significantly higher percentage of mycorrhizal colonization was recorded in the treatment where both GF and RP were present. After 45, 90, 135 and 180 days of plant growth 33.6, 52.5, 76.4 and 92.3 percent root colonization was recorded in GF+RP inoculated plants as compared to 29.2, 44.8, 63.7 and 81.9% respectively in GF alone-inoculated plants. GF and RP combination has improved plant growth, shoot and root dry weights and nutrient uptake more than in single inoculation and in uninoculated control plants.